Changing Generational Values and New Masculinities Amongst Smallholder Export Cash Crop Producers in Papua New Guinea - Koczberski, G.; Curry, George (2016)
This article is concerned with changing generational values and aspirations and intergenerational conflicts among migrant farmers in West New Britain Province, Papua New Guinea. Drawing on fieldwork amongst oil palm smallholders, the paper begins by documenting how economic pressures and a conjunction of social changes are leading younger men to challenge indigenous relations of authority and obligation that underpin father-son relationships. Rising material aspirations and revised social and economic values structured by kinship are driving this challenge by young men and making it more difficult for fathers to draw on their sons’ ‘unpaid’ labour. We then describe how these challenges are enacted through demands on fathers for new relations of production that give sons more power and control over the management of the oil palm block and the distribution of the income. These demands by an aspiring generation of young men are often contested fiercely by fathers who see such demands as weakening their authority and eroding their socio-political role in daily decision-making. We illustrate how the contemporary and highly commodified environment of migrant lives has redefined father-son relationships and forms of sociality, and contributed to intergenerational conflicts and the adoption by sons of new male identities and masculinities.